FEMINIZATION OF NILE TILAPIA Oreochromis niloticus (L.) BY DIETHYLSTILBESTROL GROWTH AND GONADOSOMATIC INDEX - Marín Ramírez, José Antonio; Alcántar Vázquez, Juan Pablo; Antonio Estrada, Carolina; Moreno de la Torre, Raúl; Calzada Ruíz, Daniel (Ecosistemas y Recursos Agropecuarios, 2015)
Sex-reversal by exogenous hormones is the most common technique used to generate monosex popu- lations of Nile tilapia (Oreochromis niloticus). However, this technique has provoked a negative perception in recent years. Because of this, alternative techniques have been developed, including the production of YY males. Although the final product (for sale) is not administered hormones, the first part of this technique still requires the feminization of XY fry by use of estrogens, including some of a synthetic nature, such as diethylstilbestrol (DES), an estrogen that has shown particularly excellent results in related species. The aim of this study was to evaluate the effect of increasing concentrations of DES (100, 200, 300, and 400 mg kg−1 during the fry stage on the sex proportion, growth and gonadosomatic index (GSI) of Nile tilapia. The 400 mg kg−1 concentration was the one that produced the highest proportion of females (91 %). However, increasing the concentration of DES provided through diet does not guarantee a 100 % feminization rate. Additionally, the growth, survival and GSI, showed a significant decrease (p < 0.05) in all groups fed with DES compared to the control group. It is possible that the anabolic effect of DES observed in other species is not present in Nile tilapia.